Designing a Pure Talent Management Model in the Growth Centers of Technological Units of Islamic Azad University with the Foundation's Data Approach - Morteza Hazrati; Sevda Sheikhi Lisar; Mohammad Taghipour (International Journal of Sustainability, 2024)
Talent management is one of the management fields that has experienced the greatest growth in the last two decades. Due to its competitive nature, for the first time the concept of talent management was proposed in private organizations and large multinational companies and was widely welcomed. Therefore, the main goal of this research is to design a lean talent management model in Islamic Azad University technology development centers with a foundation data approach. Since the current research seeks to design a lean talent management model in Islamic Azad University technology development centers with a foundation data approach and wants to provide reliable guidelines to policy makers to take corrective measures, it is considered an applied research. On the other hand, considering the increase in knowledge resulting from the design of the pure talent management model in the growth centers of technological units of Islamic Azad University with the foundation data approach, this research also has a fundamental orientation. Considering that the research implementation strategy is of a qualitative type, that is why the approach of this dissertation is an inductive approach. Since the current research is considered among qualitative researches, qualitative research strategies are also used in its conduct. The qualitative strategy used in the first stage of the research is grounded theory. The participants in this research are the heads of the growth centers of technology units of Azad University. In order to conduct sampling in the first stage of the research, theoretical sampling was used and 10 people were selected as a sample. At the end of the qualitative section, a model was designed using the foundation data approach. In the quantitative section, the research hypotheses were tested using structural equation modeling, and all of them were confirmed.
Keywords: Azad University; Foundation data theory; Pure talent management; Technology unit growth center